Analisis Kesulitan Belajar Struktur Aljabar di STKIP PAHLAWAN Tuanku Tambusai - Astuti; Sari, Nurhidayah (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2018)
The purpose of this study was to determine difficulties of learning and the factors that cause difficulties experienced by the algebraic structure to motovated student in learning process. Subject of research undertaken is the third semester students in the academic year 2015/2016. Data collection method used is documentation, test, observation and interview. The reason of student difficulties in learning algebraic structure that is on the problem-solving, concepts and skills. Most problems experienced by students is the troubleshooting sections with a percentage of 62.5%. Another difficulty experienced by students of the difficulty in concept with a percentage of 50%. The difficulties experienced by the last one is trouble on the skills students with a percentage of 45.7%.